Inhibitory effect for proliferation of oral bacteria in dogs by tooth brushing and application of toothpaste - WATANABE, Kazuhiro (J Vet Med Sci, 2016)
To investigate inhibitory effect for oral bacterial proliferation, we divided 12 dogs into 3 groups; scaling alone (C; control group), brushing (B) and application of toothpaste (P). Before scaling (Pre) and at 0 to 8 weeks after scaling (0–8 w), we collected oral bacteria from the dental surface every week and counted them using a bacterial counter. The results demonstrated a significant reduction in the number of oral bacteria for group B relative to Pre and group C, as well as for group P relative to group C at 5–7 w. Consequently, brushing may inhibit an increase in the number of oral bacteria, and toothpaste may be effective at a certain level, although not more than that of brushing.